FIELD STUDY IN SOME ENERGY PROPERTIES OF USING DISC PLOW - Ghazwan, A. Dahham (Mesopotamia Journal of Agriculture)
Field experiment was conducted to study the effect three levels of tilt angles (15°, 20° and 25°) two levels of depth (10 and 20) cm and three speeds (3.6,4.9 and 6.8) km/h according to design RCBD method of split-split block design and their effect on ; drawbar power(kw) , slippage percentage (%), fuel consumption(L/ha), specific energy area(MJ/ha), specific energy volume (KN/m3) and specific energy efficiency. Results showed that all  the studied characteristics were increased by increasing tilt angle. Different levels of depths and speeds had significant effects in all the studied characteristics, The increased of plowing depths from (10cm) to (20cm) was increased in all studied characteristics exceptionality specific energy volume. Drawbar power, slippage percentage and specific energy efficiency increased by increasing speeds, While the fuel consumption, specific energy area and specific energy volume were decreased by increasing forward speed. It was found that all interactions between (tilt angles, plowing depths and forward speed) had significant effects in all the studied characteristics.